2016
DOI: 10.1016/j.powtec.2015.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and experimental study of horizontal pneumatic transportation of spherical and low-aspect-ratio cylindrical particles

Abstract: (2016) Numerical and experimental study of horizontal pneumatic transportation of spherical and low-aspect-ratio cylindrical particles. Powder Technology, Published by: Elsevier URL:http://dx

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…x ij = (X j − X i ) • n i j is the relative distance between two particle andv i j = (v jvi )•n i j the relative predicted velocity projected along n ij . Decomposing contact forces by their amplitude f ik and direction n ik and introducing previous notations, equation (12) becomes:…”
Section: Particle Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…x ij = (X j − X i ) • n i j is the relative distance between two particle andv i j = (v jvi )•n i j the relative predicted velocity projected along n ij . Decomposing contact forces by their amplitude f ik and direction n ik and introducing previous notations, equation (12) becomes:…”
Section: Particle Interactionsmentioning
confidence: 99%
“…The interested reader is referred to [27] regarding grid size to DEM particle diameter ratio and validation of numerical model pertaining to particel bounce in a rectangular model compared with experimental data. In fact, there is no concrete consensus among the research arena regarding the modeling of solid-air drag closures [12,48,18].…”
Section: Mesh Cell Size and Dem Particle Sizementioning
confidence: 99%
“…Tsuji et al [69][70] firstly proposed this model and then many researchers have adopted this model in the studies of pneumatic conveying with millimetre-scale particle diameter, as shown in Table 3. Ebrahimi et al [72] Spherical glass Oschmann et al [73] Non-spherical Li et al [74] Spherical Tan et al [77] Spherical Tsuji [79] Polystyrene ( Langston [80] Polystyrene Li et al [83] Spherical Recently, studies about fine particle simulations have been increased. By applying CFD-DEM approach, Chen et al [84] numerically investigated the particle transport and deposition in pulmonary airway, and the simulation results were compared with experiment results.…”
Section: Granular Temperaturementioning
confidence: 99%
“…The papers within this special issue cover a significant effort by the authors, in the framework of the EU-FP7 Marie Curie ITN (Initial Training Network) PARDEM (see www.pardem.eu) in deploying various aspects of DEM. A range of industrial application examples are studied (silo flow [18], mixing [19], and segregation [20]); for large, granular particles as well as two-phase systems (fluidized beds [21] or pneumatic conveying [22]); and cohesive powders (cone penetration and unconfined strength testing [23], dosing of cohesive food powder [24]), as well as the more fundamental issues of fine powder testing with different devices and the extremely slow stress-relaxation in such systems [25]. On the macroscopic level several important questions are addressed, such as the effect of the particle size-ratio on the bulk stiffness of granular mixtures [26] as well as the asymmetry of stress tensor arising from a micropolar formulation [27].…”
Section: Overview Of the Special Issuementioning
confidence: 99%